THE ROLE OF INNOVATIVE TECHNOLOGIES IN AGRIBUSINESS DEVELOPMENT (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article highlights the economic and social importance of innovative technologies in the development of agribusiness. The use of modern technologies in agriculture has led to an increase in production efficiency, an expansion of opportunities for rational use of resources, and an increase in export potential. The role of innovative approaches in the processing, storage, and delivery of agricultural products to the market is also highlighted.